ダイ4ジ ナンキョク チイキ カンソクタイ チジキ ブモン センジョウ カンソク ホウコク - 柿沼, 清一; カキヌマ, セイイチ; 村石, 幸彦; ムライシ, ユキヒコ; KAKINUMA, Seiichi; MURAISHI, Yukihiko (国立極地研究所, 1961)
P(論文) The geomagnetic total force observations along the navigation route from Japan to the Antarctic Ocean via Singapore and Cape Town were carried out using the Proton Precession Magnetometer which was used in the second (1957-58) and the third (1958-59) expeditions for the same purpose. We got nearly the same results at the Indian Ocean as on former observations. In this paper, the results of observation from Cape Town to the Antarctic Ocean are chiefly reported. 1. We discovered about 10 discrepancy between the total force of our measurement by Proton Magnetometer and that of Hermanus Observatory, Cape Province, South Africa obtain from Variometers. Fig. 1. 2. The iso-total force lines diagram deduced from the results of observation at the second and fourth expedition are illustrated in Fig. 2. 3. The annual changes of the total force between Cape Town and the Antarctic Ocean deduced from the results at the second, third and fourth expeditions are shown in Fig. 3, where no corrections for diurnal variation are applied. 4. The tso-total force lines diagram in the Lutzow-Holm Bay deduced from the results at the second and fourth expeditions are illustrated in Fig. 4. 5. Anomaly changes of about 400 were observed which are presumed to be caused by the submarine relief. Two examples are illustrated in Fig. 5. departmental bulletin paper